2012
DOI: 10.1128/mcb.00737-12
|View full text |Cite
|
Sign up to set email alerts
|

Geminin Regulates the Transcriptional and Epigenetic Status of Neuronal Fate-Promoting Genes during Mammalian Neurogenesis

Abstract: Regulating the transition from lineage-restricted progenitors to terminally differentiated cells is a central aspect of nervous system development. Here, we investigated the role of the nucleoprotein geminin in regulating neurogenesis at a mechanistic level during both Xenopus primary neurogenesis and mammalian neuronal differentiation in vitro. The latter work utilized neural cells derived from embryonic stem and embryonal carcinoma cells in vitro and neural stem cells from mouse forebrain. In all of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
(71 reference statements)
0
21
0
1
Order By: Relevance
“…Previously, we demonstrated that Geminin has a role in regulating the epigenetic status, expression, or activity of critical transcription factors during primary neurogenesis in Xenopus and also during in vitro mouse ES cell differentiation towards neuroectoderm (Lim et al, 2011; Seo et al, 2005; Yellajoshyula et al, 2012, 2011). However, analyzing Geminin's in vivo function in mammals was hampered due to the preimplantation lethality of Geminin null embryos (Gonzalez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that Geminin has a role in regulating the epigenetic status, expression, or activity of critical transcription factors during primary neurogenesis in Xenopus and also during in vitro mouse ES cell differentiation towards neuroectoderm (Lim et al, 2011; Seo et al, 2005; Yellajoshyula et al, 2012, 2011). However, analyzing Geminin's in vivo function in mammals was hampered due to the preimplantation lethality of Geminin null embryos (Gonzalez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…After the ChIP step, the recovered chromatin samples were subjected to qPCR (ChIP-qPCR) using specific primers (Supplemental Table 2). The percent-input values were calculated as described previously [18]. The qPCR data for each primer pair were represented as percent-input by calculating each specific DNA fragment in immunoprecipitates relative to that in input DNA.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…Antagonism between Geminin and Brg1 has also been proposed to control acquisition of trophoectoderm markers and maintain expression of the core pluripotency genes in mouse embryonic stem (ES) cells [42]. In a recent study by Kroll's group, it was suggested that Geminin antagonizes bHLH transcription factors that promote neurogenesis by maintaining the bivalent status of their promoters [43].…”
Section: Developmental Roles Of Pre Rc Componentsmentioning
confidence: 98%